Analisis Risiko Usaha Tani Jagung Di Desa Lompad Baru Kecamatan Ranoyapo Kabupaten Minahasa Selatan - Kaban, Natasha Dian Rudangta; Katiandagho, Theodora Maulina; Baroleh, Jenny (Sam Ratulangi University, 2023)
This study aims to determine the income of corn farming farmers, the risks faced by corn farming farmers, and how much risk is faced by farmers. The research was conducted in Lompad Baru Village, Ranoyapo District, South Minahasa Regency. This research was conducted from April to August 2022. The selection of respondents was intentional. Primary data is data obtained directly from the field through interviews using a questionnaire to each corn farming farmer. Secondary data, namely data obtained through related agencies such as the field agricultural extension office in Ranoyapo District and the Lompad Baru Village office. The results showed that the total income earned by all corn farming farmers was IDR14,200,000 with an average income earned by corn farming farmers amounting to IDR1,420,000. The risks of corn farming in the study area are production risks originating from disturbances of plant-disturbing organisms (pests, diseases and weeds), erratic weather/climate (long dry spells) and minimal availability of subsidized seeds; price/market risk stems from high corn fertilizer prices and high pesticide prices; institutional risk; human risk; financial risk. The level of income risk faced by corn farming farmers is low with a coefficient of variation (KV) of 0.56.